2004
DOI: 10.1111/j.1467-9957.2004.00411.x
|View full text |Cite
|
Sign up to set email alerts
|

Job Creators

Abstract: Job creation is perhaps the key political and economic issue of our time, yet this is one of only three papers to date to consider the nature of job creation amongst the self-employed. We develop a utility based model of self-employment which allows for the self-employed with employees. The theory predicts that the higher the endowment of human capital the greater the likelihood of the entrepreneur employing additional labour, subject to overcoming any capital constraints. Empirical testing suggests that the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 27 publications
5
43
1
2
Order By: Relevance
“…Employers comprise the minority of the self-employed in most countries, including Spain; but they are usually associated with greater economic value-added (Cowling et al, 2004). We found that in Spain employer self-employment rates evolve pro-cyclically whereas own-account self-employment rates evolve counter-cyclically.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Employers comprise the minority of the self-employed in most countries, including Spain; but they are usually associated with greater economic value-added (Cowling et al, 2004). We found that in Spain employer self-employment rates evolve pro-cyclically whereas own-account self-employment rates evolve counter-cyclically.…”
Section: Discussionmentioning
confidence: 73%
“…In which case, one might expect the number of employer entrepreneurs to increase relative to the number of own-account entrepreneurs, making cyclical effects positive for employer entrepreneurs and negative for own-account entrepreneurs. And to the extent that more favorable economic conditions improve opportunities for some own-account entrepreneurs as well, we might expect some own-account entrepreneurs to start hiring labor (Cowling et al, 2004), in which case they switch from own-account to employer status, and reinforce the positive cyclical effects for employers and the negative cyclical effects for the own-account group. Our empirical estimates below will shed light on these conjectures.…”
Section: Persistence Hysteresis Business Cycles and Entrepreneurshipmentioning
confidence: 99%
“…Several entrepreneurship studies hint at the existence of segmentation within the self-employment sector and distinguish between the self-employed who monitor others and own-account workers (Banerjee & Newman, 1993;Earle & Sakova, 2000;Cowling et al, 2004;Congregado, Millán & Román, 2010). This distinction between employers and own-account workers is considered to be relevant, for example, to understand the role that entrepreneurs play in markets and in the process of economic development.…”
Section: Literature Background Segmentation Within Self-employmentmentioning
confidence: 99%
“…The common theoretical explanation for credit rationing vis-a-vis newly founded firms is a severe lack of observable and verifiable information about the entrepreneur's type, her plans, and the risks associated. The asymmetry of information on the entrepreneur's type and behavior will potentially lead to agency problems: adverse selection and moral hazard (Leroy and Singell [1987]; Boadway et al [1998] Burke, FitzRoy, and Nolan [2002]; CGW: Coopers, Gimenogascon, and Woo [1994]; C; Cressy [1996]; EJ: Evans and Jovanovic [1989]; HJR: Holtz-Eakin, Joulfaian, and Rosen [1994a]; LO: Lindh and Ohisson [1996]; T: Taylor [1999]; vP: Van Praag [2003]; CTM: Cowling, Taylor, and Mitchell [2004], Meza and Webb [2000]). The foresight of these problems might prevent the start of ventures.-'…”
Section: Theorymentioning
confidence: 99%